2004
DOI: 10.2166/wst.2004.0310
|View full text |Cite
|
Sign up to set email alerts
|

Combined biological and physico-chemical treatment of baker's yeast wastewater including removal of coloured and recalcitrant to biodegradation pollutants

Abstract: The UASB reactor (35 degrees C) was quite efficient for removal of bulk COD (62-67%) even for such high strength and recalcitrant wastewater as the cultivation medium from the first separation process of baker'syeasts (the average organic loading rates varied from 3.7 to 10.3 g COD/l/d). The aerobic-anoxic biofilter (20 degrees C) can be used for removal of remaining BOD and ammonia from strong nitrogenous anaerobic effluents; however, it suffered from COD-deficiency to fulfil denitrification requirements. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 2 publications
2
12
0
Order By: Relevance
“…Therefore, it is necessary to apply more effective processes for the destruction of color and refractory organics to comply with the discharge limits. For example biological purification can be used in combination with other processes such as physico-chemical [4,5], membrane [6], electrochemical [7][8][9], or advanced oxidation processes [10][11][12][13][14]. But many of the above treating methods are expensive beyond the fmancial capacity of enterprises, which limits their wide-spread application to yeast wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to apply more effective processes for the destruction of color and refractory organics to comply with the discharge limits. For example biological purification can be used in combination with other processes such as physico-chemical [4,5], membrane [6], electrochemical [7][8][9], or advanced oxidation processes [10][11][12][13][14]. But many of the above treating methods are expensive beyond the fmancial capacity of enterprises, which limits their wide-spread application to yeast wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The second is low to moderate process wastewater coming from cleaning. The dark brown color in these wastewaters is caused by the pigment called melanoidins which is resistant in nature, and it is not biodegradable [3], [4]. Some researchers studied color and COD removals from Bakery Yeast wastewater by using biological treatment alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…Baker`s yeast industry wastewater has high BOD and COD. Gladchenko et al (2004) reported wastewaters with high strength in the range of 10 to 80 g COD/L, strong nitrogenous ranging from 0.5 to 1.5 g/L total N, sulphaterich (2 to 10 g/L), phosphorus variable (sometimes Pdeficient), recalcitrant for biodegradation and highly coloured. Dairy industry whey wastewater has a typical white colour and a high nutrient level as well as organic matter content (Najafpour et al, 2009).…”
Section: Introductionmentioning
confidence: 99%